A systemic review and recommendation for an autopsy approach to death followed the COVID 19 vaccination. (November 2022) - Tan, Lii Jye; Koh, Cai Ping; Lai, Shau Kong; Poh, Woon Cheng; Othman, Mohammad Shafie; Hussin, Huzlinda
Abstract: The outbreak of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) started in December 2019. An immediate prevention approach for the outbreak is the development of a vaccination program. Despite a growing number of publications showing the effectiveness of vaccination in preventing SARS-CoV-2 outbreak and reducing the mortality rate, substantial fatal adverse effects were reported after vaccination. Confirmation of the causal relationship of death is required to reimburse under the national vaccination program and could provide a reference for the selection of vaccination. However, a lack of guidelines in the laboratory study and autopsy approach hampered the investigation of post-vaccination death. In this paper, we performed a systematic electronic search on scientific articles related to severe Covid-19 vaccination adverse effects and approaches in identifying the severe side effects using PubMed and Cochrane libraries. A summary on the onset, biochemistry changes and histopathological analyzes of major lethally side effects post-vaccination were discussed. Ultimately, a checklist is suggested to improve the quality of investigation Highlights: Polysorbate and Polyethylene glycol could potentially induce allergic reaction. Vaccine induced thrombotic thrombocytopenia result in formation of antiplatelet factor 4 leading to thrombosis. VITT was frequently reported in adenoviral- based vector vaccines. Myocarditis is generally observed in mRNA vaccine.